2010
DOI: 10.1080/07325221003730285
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Processes in Triadic Supervision

Abstract: During a four-year research project that grew out of their teaching and supervision, three counselor educators used a constructivist grounded theory approach to address a gap in the literature on triadic supervision. The authors collaborated with 2 research assistants and 28 research participants to examine triadic supervision through analysis of individual and focus group interviews, observation of videotapes of triadic supervision, and ongoing discussions. Analysis and interpretive theorizing resulted in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 6 publications
2
17
0
Order By: Relevance
“…Findings from the current study parallel past research Oliver et al, 2010) in which triadic supervision fostered a sense of community. Through collaboration and shared responsibility, all triadic members may provide enhanced authentic feedback, encouraging supervisees to move forward in their counseling work.…”
Section: Feedback and Learning Opportunitiessupporting
confidence: 74%
See 2 more Smart Citations
“…Findings from the current study parallel past research Oliver et al, 2010) in which triadic supervision fostered a sense of community. Through collaboration and shared responsibility, all triadic members may provide enhanced authentic feedback, encouraging supervisees to move forward in their counseling work.…”
Section: Feedback and Learning Opportunitiessupporting
confidence: 74%
“…Triadic supervision generally has resulted in insightful, valuable, challenging feedback while supportive to the growth of supervisees Goldberg et al, 2012). Triadic supervisors have noted that feedback between and among the triad often complemented each other and created a dynamic synergy that enhanced learning and fostered a sense of community within the time constraints of a supervision session (Oliver et al, 2010).…”
Section: Journal Of Counselor Preparation and Supervision Volume 7 mentioning
confidence: 99%
See 1 more Smart Citation
“…Such supervision has been described as having the potential to transform the professional and social identities of both the supervisor and supervisee (Carroll, 2010) through "dialogical exchange" (Palmer, 2007, p. 79). Oliver, Nelson, and Ybañez (2010) referred to this dialogic exchange when they noted, "interaction among supervisor and supervisees impacts each of the people in the room, which then impacts the next interaction, which then impacts each of the people in the room and so on" (p. 61). This recursive phenomenon of co-constructing supervisory communication, including understandings of supervisees' experiences, has been referred to as re-authoring across constructivist, postmodern approaches to supervision (Fox, Tench, & Tench, 2002;Knight, 2004;Speedy, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…Doctoral supervisors also reported that managing feedback and relationship dynamics was especially demanding. Oliver, Nelson, and Ybañez (2010) similarly concluded that competency in working effectively with relationship disruptions between supervisees was a unique and essential skill for triadic supervisors.…”
mentioning
confidence: 99%